Peptide receptor radionuclide therapy of treatment-refractory metastatic thyroid cancer using (90)Yttrium and (177)Lutetium labeled somatostatin analogs: toxicity, response and survival analysis - Budiawan, Hendra (e-Century Publishing Corporation, 2013)
The overall survival rate of non-radioiodine avid differentiated (follicular, papillary, medullary) thyroid carcinoma is significantly lower than for patients with iodine-avid lesions. The purpose of this study was to evaluate toxicity and efficacy (response and survival) of peptide receptor radionuclide therapy (PRRT) in non-radioiodine-avid or radioiodine therapy refractory thyroid cancer patients. Sixteen non-radioiodine-avid and/or radioiodine therapy refractory thyroid cancer patients, including follicular thyroid carcinoma (n = 4), medullary thyroid carcinoma (n = 8), Hürthle cell thyroid carcinoma (n = 3), and mixed carcinoma (n = 1) were treated with PRRT by using (90)Yttrium and/or (177)Lutetium labeled somatostatin analogs. (68)Ga somatostatin receptor PET/CT was used to determine the somatostatin receptor density in the residual tumor/metastatic lesions and to assess the treatment response. Hematological profiles and renal function were periodically examined after treatment. By using fractionated regimen, only mild, reversible hematological toxicity (grade 1) or nephrotoxicity (grade 1) were seen. Response assessment (using EORTC criteria) was performed in 11 patients treated with 2 or more (maximum 5) cycles of PRRT and showed disease stabilization in 4 (36.4%) patients. Two patients (18.2%) showed partial remission, in the remaining 5 patients (45.5%) disease remained progressive. Kaplan-Meier analysis resulted in a mean survival after the first PRRT of 4.2 years (95% CI, range 2.9-5.5) and median progression free survival of 25 months (inter-quartiles: 12-43). In non-radioiodine-avid/radioiodine therapy refractory thyroid cancer patients, PRRT is a promising therapeutic option with minimal toxicity, good response rate and excellent survival benefits.